ANALYSIS OF REGIONAL AUTHORITY IN THE FORMATION OF LOCAL REGULATIONS BASED ON PANCASILA IDEOLOGY: ANALISIS KEWENANGAN DAERAH DALAM PEMBENTUKAN PERATURAN DAERAH YANG BERLANDASKAN IDEOLOGI PANCASILA - Putra, Rengga Kusuma; Saragih, Geofani Milthree (Constitutional Law Society, 2025)
This research analyses the local authority in the formation of local regulations (Perda) based on the ideology of Pancasila. As a country with a decentralised system, Indonesia gives authority to local governments to form local regulations according to the needs of each region. However, in its implementation, this authority must remain in line with the principles contained in Pancasila as the basis of the state. This research uses normative legal research method with statute approach and conceptual approach. The data source used is secondary data consisting of laws and regulations, court decisions, and relevant legal literature. The results show that in the formation of local regulations, local governments must pay attention to the principles of the formation of good laws and regulations as stipulated in Law Number 12 of 2011 concerning the Formation of Laws and Regulations. In addition, there is a supervisory mechanism from the central government and the Supreme Court to ensure that the Perda formed does not conflict with higher regulations and the values of Pancasila. This research recommends strengthening the synergy between local and central government in drafting local regulations, as well as increasing public participation to ensure that any local regulations formed truly reflect the values of Pancasila and the interests of the community at large.